2019
DOI: 10.1136/heartjnl-2019-315036
|View full text |Cite
|
Sign up to set email alerts
|

Acute versus chronic myocardial injury and long-term outcomes

Abstract: ObjectiveThere is a paucity of data regarding prognosis in patients with acute versus chronic myocardial injury for long-term outcomes. We hypothesised that patients with chronic myocardial injury have a similar long-term prognosis as patients with acute myocardial injury.MethodsIn an observational cohort study of 22 589 patients who had high-sensitivity cardiac troponin T (hs-cTnT) measured in the emergency department during 2011–2014, we identified all patients with level >14 ng/L and categorised them as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
7
23
1
Order By: Relevance
“…Troponin elevation is common in conditions other than acute coronary syndromes. A number of studies in both selected and unselected populations suggest that non-ischaemic myocardial injury is the most common cause of elevation in cardiac troponin concentration, [ 9 , 16 , 17 , 18 , 19 ], with more recent studies discriminating between acute and chronic myocardial injury [ 21 , 22 , 23 , 24 ] ( Table 1 ). In an observational cohort study of 22,589 patients who had hs-cTnT measured in a single emergency department (ED) in Sweden [ 22 , 23 ], 65% of those with elevated cardiac troponin concentrations had myocardial injury (30% acute and 35% chronic), with the remaining 35% having a diagnosis of myocardial infarction.…”
Section: Epidemiology Of Acute and Chronic Myocardial Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Troponin elevation is common in conditions other than acute coronary syndromes. A number of studies in both selected and unselected populations suggest that non-ischaemic myocardial injury is the most common cause of elevation in cardiac troponin concentration, [ 9 , 16 , 17 , 18 , 19 ], with more recent studies discriminating between acute and chronic myocardial injury [ 21 , 22 , 23 , 24 ] ( Table 1 ). In an observational cohort study of 22,589 patients who had hs-cTnT measured in a single emergency department (ED) in Sweden [ 22 , 23 ], 65% of those with elevated cardiac troponin concentrations had myocardial injury (30% acute and 35% chronic), with the remaining 35% having a diagnosis of myocardial infarction.…”
Section: Epidemiology Of Acute and Chronic Myocardial Injurymentioning
confidence: 99%
“…Most studies demonstrate that cardiovascular death and recurrent myocardial infarction are more common in patients with type 1 myocardial infarction, but patients with both acute and chronic myocardial injury have a substantially higher risk than those without myocardial injury [ 21 , 22 , 23 , 75 ].…”
Section: Clinical Outcomes In Patients With Myocardial Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledgment of the double-edged mechanism of the inflammation in MI is clinically important as heart failure (HF) patients with reperfusion surgery have poor prognoses. This therefore presents medical practitioners with significant therapeutic challenges (Kadesjö et al, 2019). Results from clinical trials targeting inflammatory factors in MI are inconsistent and not always in line with initial hypotheses.…”
Section: Prevention Of Cardiovascular Events Via Anti-inflammationmentioning
confidence: 99%
“…Ischemic heart diseases, particularly myocardial infarction (MI), remain a primary factor for mortality and morbidity worldwide. A recent observational study of a European cohort revealed similar mortality rates (∼49%) for both acute and chronic MI, highlighting the poor prognosis (Kadesjö et al, 2019). The American Heart Association reported that one third of total deaths for individuals over 35 years of age in the United States were associated with cardiovascular disorder (CVD) (Benjamin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%